Electrode interface optimization advances conversion efficiency and stability of thermoelectric devices - Jing Chu (Nature Portfolio, 2020)
Long-term service stability of thermoelectric devices is one of the major obstacles for their application. Here, the authors combine interfacial reaction energy and Sb migration activation energy barrier as a criterion to determine the interfacial reliability for skutterudite thermoelectric devices.